PERAN KOMPETENSI KEPRIBADIAN GURU DALAM PEMBENTUKAN KARAKTER DISIPLIN PESERTA DIDIK DI SDK BOTUNG - Maria Magdalena Wola; Yohanes Maria Vianney Benolo Watun; Krisantus Minggu Kwen (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to describe the role of teachers' personality competencies in shaping the disciplinary character of students at SDK Botung. The research method used is descriptive qualitative, with data collection techniques consisting of observation, interviews, and documentation. Based on the data obtained, teachers' personality competencies are very important in shaping character, one of which is the discipline of students both in terms of time, dress, and speech, both within and outside the school environment. Good personality traits demonstrated by teachers will set a good example for students. Teachers will become figures who are obeyed in all their wisdom, advice, words and commands. It is hoped that the personality competencies possessed by teachers can shape the discipline of students, so that the learning process can run well and teachers can transfer their knowledge and be accepted by their students.